1978
DOI: 10.1021/ja00477a034
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic aromatic substitution by organostannylsodiums. A second-order reaction displaying a solvent cage effect

Abstract: Results of a study of mechanistic aspects of the reaction of triorganostannylsodiums with halobenzenes are reported. The reaction in tetraglyme, which is first order in each reactant, is unusually fast for an unactivated nucleophilic aromatic substitution, and provides high yields of arylstannanes, R3SnAr. Minor amounts of R3SnAr2 and R4Sn are also formed by a mechanism which is presumed to involve initial dissociation of R3SnNa into (RzSn) and RNa. Reduction product, ArH, is formed when effective proton donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Thus, for the reactions of the Me 3 Sn À anion with halobenzenes the mechanism with halogen transfer in the solvent cage as a key step was established by Kuivila et al [29] The effect of MeCN, similar to that observed in our study, has been reported in the reaction of another metal-centred nucleophile, [Re(O)(R ± CC ± R) 2 ] À (R Et, Ph) with halobenzenes. [30] Instead of the s-aryl rhenium complex observed in benzene solution, when the reaction was carried out in MeCN cyanomethyl complex NCCH 2 ± [Re(O)(RCCR) 2 ] was formed with the equivalent amount of benzene.…”
supporting
confidence: 87%
“…Thus, for the reactions of the Me 3 Sn À anion with halobenzenes the mechanism with halogen transfer in the solvent cage as a key step was established by Kuivila et al [29] The effect of MeCN, similar to that observed in our study, has been reported in the reaction of another metal-centred nucleophile, [Re(O)(R ± CC ± R) 2 ] À (R Et, Ph) with halobenzenes. [30] Instead of the s-aryl rhenium complex observed in benzene solution, when the reaction was carried out in MeCN cyanomethyl complex NCCH 2 ± [Re(O)(RCCR) 2 ] was formed with the equivalent amount of benzene.…”
supporting
confidence: 87%
“…Decreasing the bulk of the alkyltin substituent has been shown to increase the rate of iododestannylation (17,28) Although the astatination of mAbs has been reported (29)(30)(31), retention of immunocompetence after 211At labeling was not demonstrated. In the present study, we have shown that 81C6 IgG2b mAb and Mel-14 IgG2a F(ab')2 fragment can be labeled with 211At and retain their specific binding to human glioma homogenates in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Their ability to react with unactivated aryl and vinyl halides, which are inert towards conventional nucleophiles, forms another aspect of their exceptional nucleophilic reactivity. [6][7][8][9][10][11][12][13][14] The term "supersoftness" is used to refer to much higher affinity of metal-centred anions towards organic substrates with soft leaving groups, e.g. higher than usual k I /k OTos or k I /k Br ratios.…”
Section: Introductionmentioning
confidence: 99%
“…higher than usual k I /k OTos or k I /k Br ratios. While evident already in aliphatic S N 2 reactions, [4][5][6]15 in aromatic and vinylic substitution with metal centred anions the leaving group effect is often reversed: from F>>Cl, Br, I typical for Ad N E mechanism it changes to I>Br>Cl>F. [6][7][8]12,[14][15][16][17][18] The last but not least is the high reducing power of metal-centred nucleophiles. Their reactions with organic halides formally considered as nucleophilic are frequently accompanied by the formation of dehalogenated or homocoupled products.…”
Section: Introductionmentioning
confidence: 99%